Chronic crisis management in Malaysia revisited - Fontaine, Rodrigue Ancelot Harvey (Malaysian Institute of Management, 2016)
Fontaine (2012) found that chronic crisis management – when problems are hidden from management rather than solved – is a salient feature of the Malaysian workplace. This study replicates the study of Fontaine (2012) to find out how the situation has evolved over the last four years. A total of 538 respondents in the Klang Valley participated in this study. The general conclusion is that chronic crisis management (mean of 3.54 on a 5 point Liker scale) and other structural problems are still very much the norm. These problems seem to be worse in smaller organisations (F 3.39 and sig. of 0.034). On the plus side, Malaysian employees are optimistic about the future (mean of 3.64) and ready to change. ANOVAs show differences between the perceptions of managers with more than 10 subordinates and their subordinates. ANOVAs show differences between the perceptions of respondents in organisations with more than 500 employees and smaller organisations. A number of suggestions, based on the data collected and on the literature, are proposed to solve these problems. In particular, this author suggests the performance management system be changed to cease rewarding employees who simply hide problems.